2021
DOI: 10.1186/s13054-021-03466-z
|View full text |Cite
|
Sign up to set email alerts
|

Bedside POCUS during ward emergencies is associated with improved diagnosis and outcome: an observational, prospective, controlled study

Abstract: Background Rapid response teams are intended to improve early diagnosis and intervention in ward patients who develop acute respiratory or circulatory failure. A management protocol including the use of a handheld ultrasound device for immediate point-of-care ultrasound (POCUS) examination at the bedside may improve team performance. The main objective of the study was to assess the impact of implementing such a POCUS-guided management on the proportion of adequate immediate diagnoses in two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 46 publications
(64 reference statements)
2
57
0
10
Order By: Relevance
“…Several preliminary studies suggest benefits of HHU use. These include reduced need for follow-up testing when used in the outpatient setting, with a low incidence of false negatives (5%), and faster time to diagnosis and reduced time to first intervention when HHUs were used by rapid response teams [ 66 , 67 ]. While image interpretability appears similar between HHUs and cart-based systems, a critical concept for future studies is not to conflate image quality and the setting of use with operator training and skills [ 68 ].…”
Section: Future Of Handhelds In the Edmentioning
confidence: 99%
“…Several preliminary studies suggest benefits of HHU use. These include reduced need for follow-up testing when used in the outpatient setting, with a low incidence of false negatives (5%), and faster time to diagnosis and reduced time to first intervention when HHUs were used by rapid response teams [ 66 , 67 ]. While image interpretability appears similar between HHUs and cart-based systems, a critical concept for future studies is not to conflate image quality and the setting of use with operator training and skills [ 68 ].…”
Section: Future Of Handhelds In the Edmentioning
confidence: 99%
“…There are multiple studies evaluating the use of POCUS in the ICU and ER department, until now only two studies focused on the use of POCUS during MET calls. Zieleskiewicz et al published a paper [ 14 ] in which they evaluated the effect on diagnostic adequacy of thoracic POCUS during MET calls. As in our study, they found a significant increase in the number of correct diagnosis when POCUS was used (80% versus 94%).…”
Section: Discussionmentioning
confidence: 99%
“…The role of POCUS for instance during MET calls has not been investigated extensively yet, even though its role in the emergency room (ER) and intensive care unit (ICU) is well established [ 5 13 ]. Recently, Zieleskiewicz et al published the first prospective observational study on the effect of the use of a multi-organ POCUS protocol during MET calls [ 14 ]. In this study, the use of a multi-organ POCUS protocol improved diagnostic accuracy of the MET significantly.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In a recent study, management of ward emergencies with a PUD showed an improvement in mortality (ref LZ). 9 For echocardiography, the position statement of the European Association of Cardiovascular Imaging is that the dissemination of appropriate PUD use is inevitable and desirable because of its potential impact on patient management. 9 In view of the increasing quality of these devices and POCUS development, some authors believe that PUD will supplant the stethoscope in the coming years.…”
Section: Introductionmentioning
confidence: 99%
“…9 For echocardiography, the position statement of the European Association of Cardiovascular Imaging is that the dissemination of appropriate PUD use is inevitable and desirable because of its potential impact on patient management. 9 In view of the increasing quality of these devices and POCUS development, some authors believe that PUD will supplant the stethoscope in the coming years. 10 To train physicians to use FoCUS with a PUD, it is unclear whether it is preferable to teach FoCUS to medical students using a PUD or a conventional ultrasound device (CUD).…”
Section: Introductionmentioning
confidence: 99%